(untitled) (المجلة الدولية للبحوث العلمية, 2023)
This paper is mainly concerned with the asymptotic stability of the zero solution on the eq.(1.1), as follows we have to mutate eq. (1.1) to an integral mapping equation appropriate for the contraction mapping theorems. This article is organized as follows: Section 2 presents the hypotheses to be used in the later sections, it also introduces Lemma 2.1 that converts eq. (1.1) into an essential equation, and Section 3 presents the main results.